TRIFOCAL BONE TRANSPORT - Tawil, Basir (International Journal of Allied Health Sciences, 2021)
Bone Transport using Ilizarov External Fixator has been widely used as a method to reconstruct large segmental defect of extremities in various situation including trauma, infection, and tumour. Bone Transport has many advantages including the unlimited amount of bone regeneration, early physiotherapy and weight bearing. Although distraction osteogenesis provides a highly satisfactory means of reconstructing segmental bone defects, prolonged use of Ilizarov External Fixator will decrease the patient’s compliance and inviting many complications such as pin-tract infections, hypoplastic bone formation, muscle atrophy and joint contractures. To reduce the period of external fixation, Trifocal Bone Transport technique is one of the options to overcome these challenges. Trifocal Bone Transport reduces external fixation times as it offers faster docking contact, early docking union and faster as well as better bone consolidation at each segment of distraction. These advantages overweight the disadvantages such as more complex frame assembly, additional osteotomy site and additional operating time.